2003
DOI: 10.1046/j.1365-2265.2003.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decline of vasopressin secretion in familial autosomal dominant neurohypophyseal diabetes insipidus presenting a novel mutation in the vasopressin‐neurophysin II gene

Abstract: Our data demonstrate a gradual vasopressinergic deficiency due to a novel mutation in the AVP-NPII gene in a Brazilian family with FNDI. The accumulation of A68P mutated precursor might have a cytotoxicity effect, leading to a gradual death of magnocellular neurones, and a progressive decline in AVP secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…In addition, intrafamilial variability of the age of onset of DI has been described, which may result from interactions with other genetic or environmental factors. The loss of AVP secretion is a gradual process with partial DI evolving towards complete AVP deficiency over time (16)(17)(18). According to the neurotoxicity hypothesis, the gradual accumulation of cytotoxic mutant AVP protein in the magnocellular neurons accounts for both the progressive nature and the dominant inheritance of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intrafamilial variability of the age of onset of DI has been described, which may result from interactions with other genetic or environmental factors. The loss of AVP secretion is a gradual process with partial DI evolving towards complete AVP deficiency over time (16)(17)(18). According to the neurotoxicity hypothesis, the gradual accumulation of cytotoxic mutant AVP protein in the magnocellular neurons accounts for both the progressive nature and the dominant inheritance of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The fl uid deprivation test was characteristic of AVP defi ciency as well as the absence of the hyper signal in the posterior pituitary. Family adjustment to polyuria and, consequently, polydipsia is an interesting fi nding in these cases and can be associated to progressive establishment of disease, which is corroborated by previous reports on gradual decline in vasopressin secretion (2). Most of the relatives have not realized that they had polydipsia because this was the familiar pattern of water ingestion, and they were studied only after the proband was investigated in our Service.…”
Section: Discussionmentioning
confidence: 72%
“…This familial disorder generally occurs some months to years after birth, and ongoing progressive AVP defi ciency has been described (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Since the mutation in this gene was first reported in 1991 by Ito et al [3], there have been 46 different mutations identified to date [2,[4][5][6][7][8]. Although the majority of mutations are located in the coding sequence of the signal peptide or the NPII domain [2], 18 different allelic variants are reported [2].…”
Section: Neurohypophyseal Diabetes Insipidus (Ndi) Is Caused By a Defmentioning
confidence: 99%